Case report: Early-onset Parkinson's disease with initial spastic paraparesis and hyperreflexia caused by compound heterozygous PRKN-gene exon 2 and 4 deletions - Jensen, Ida; Hendrich, Corinna; Klietz, Martin; Berding, Georg; Höglinger, Günter U.; Wegner, Florian (Frontiers in Neurology, 2022)
Pathogenic variants in the Parkin-gene (PRKN) are among the most common genetic causes of early onset Parkinson's disease (EOPD). Patients with EOPD can present with atypical clinical features and misdiagnosis is frequent. Here, we report a clinical phenotype with atypical signs and symptoms of a 35-year-old male patient with EOPD caused by a compound heterozygous PRKN-gene deletion of exons 2 and 4. After the initial diagnosis of stiff person syndrome, the patient was admitted to our department for a second opinion after 8 years of untreated disease progression. The patient presented with prominent spastic paraparesis pronounced on the right side and hyperreflexia as well as Parkinsonism with rigidity predominantly affecting the upper limbs, bradykinesia, and resting tremor. In the diagnostic assessment, magnetic evoked potentials to the anterior tibial muscles showed a low amplitude on the right side, compatible with pyramidal tract disturbance. However, an MRI of the head and the spine did not show any pathologies or atrophy. A [123I] FP-CIT SPECT scan revealed profoundly and left-pronounced reduced striatal uptake suggesting a neurodegenerative Parkinson's syndrome. Even though an acute levodopa challenge did not show marked improvement of symptoms, the chronic levodopa challenge with up to 450 mg/day significantly reduced the rigidity and bradykinesia. Surprisingly, spastic paraparesis and hyperreflexia diminished under dopaminergic treatment. Finally, genetic analysis by next-generation sequencing via copy number variant analysis (CNV) and multiplex ligation-dependent probe amplification (MLPA) confirmed compound heterozygous deletions of exons 2 and 4 in the PRKN-gene. As presented in this case, the awareness of atypical clinical symptoms of EOPD is essential to prevent misdiagnosis in young patients.